2012
DOI: 10.1212/wnl.0b013e318278b618
|View full text |Cite
|
Sign up to set email alerts
|

Ataxin-1 and ataxin-2 intermediate-length PolyQ expansions in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a relentlessly progressive neurodegenerative disorder of motor neurons, leading to a severe muscle weakness and atrophy. 1 Several mutated genes (e.g., Cu/Zn SOD1, FUS/TLS, TARDBP, C9ORF72) have been demonstrated to be implicated in the disease. [1][2][3][4] A recent work demonstrated that TDP-43, a TARDBP gene product, and ataxin-2 (ATXN-2) form a complex that depends on RNA binding and that a small number of patients with ALS are carriers of ATXN-2 intermediate expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 27 publications
3
50
1
1
Order By: Relevance
“…Several of the aforementioned studies highlighted that ATXN2 repeat length did not appear to influence clinical characteristics, including age at onset and survival after onset (Chen et al, 2011; Conforti et al, 2012; Corrado et al, 2011; Daoud et al, 2011; Gispert et al, 2012; Lee et al, 2011; Liu et al, 2013; Soraru et al, 2011; Van Damme et al, 2011), which is well in line with our present findings. Furthermore, our results are consistent with reports that did not find associations between ATXN2 repeat lengths and FTD (Ross et al, 2011; Van Langenhove et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Several of the aforementioned studies highlighted that ATXN2 repeat length did not appear to influence clinical characteristics, including age at onset and survival after onset (Chen et al, 2011; Conforti et al, 2012; Corrado et al, 2011; Daoud et al, 2011; Gispert et al, 2012; Lee et al, 2011; Liu et al, 2013; Soraru et al, 2011; Van Damme et al, 2011), which is well in line with our present findings. Furthermore, our results are consistent with reports that did not find associations between ATXN2 repeat lengths and FTD (Ross et al, 2011; Van Langenhove et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…20 Because of the presence of TDP-43 inclusions in many neurodegenerative diseases and the heterogeneity of their clinical presentation, a number of studies have evaluated ATXN2 repeat sizes in patients with neurodegenerative diseases. 17,[21][22][23][24][25][26][27][28][29][30][31][32][33] All the studies confirmed a significant association between intermediary repeat lengths and ALS, which is even stronger when familial cases are considered separately from sporadic cases. An association has also been found with PSP.…”
Section: Figurementioning
confidence: 70%
“…The authors went on to describe that the degree of ATXN2 polyglutamine expansion was correlated with the extent of TDP-43 toxicity in both Drosophila and yeast models. Furthermore, ATXN2 intermediate repeat expansion was confirmed as a risk factor in ALS patients [20,106,[144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159], and more recently as a possible modifier of C9orf72 repeat expansion toxicity in ALS/FTD [107,108].…”
Section: Reviewmentioning
confidence: 91%